Torakochirurgia Is continuous irrigation drainage of the mediastinum a safe and effective method for the treatment of descending necrotizing mediastinitis? - Rokicki, Marek; Rokicki, Wojciech; Gawrychowski, Jacek; Filipowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Introduction: Descending necrotizing mediastinitis (DNM) is a primary complication of cervical or odontogenical toxic infections that can spread to the mediastinum which is fraught with impressive morbidity and mortality rates of 30% to 40% or more. This is the report on a new combined surgical procedure consisting of cervical drainage, an aggressive mediastinal debridement via posterolateral thoracotomy plus continuous mediastinal irrigation Material and methods: Between 1999 and 2005 in our department this technique was used to treat nine patients with DNM. Results: The mean duration from first symptoms or: from the appearance of first symptoms to operation was 5 days (range 2-14), mean irrigation mediastini 9.5 days (range 5-14) and mean hospital stay was 24.4 days (range 5-39). Postoperative complications were found in four patients: three with infection post thoracotomy wound and one with pneumonia. Two patients died in the postoperative period: one died of multiorgan failure and the other of ARDS. Conclusions: Radical surgical debridement mediastini and a continuous, mediastinal irrigation drainage seem a safe and effective method for the treatment of DNM.